THE EFFECT OF MORAL DISENGAGEMENT ON BULLYING BEHAVIOR TENDENCY WITH EMPATHY AS A MEDIATOR ON STUDENTS IN PEKALONGAN CITY - Kuasandra, Manna Kurnia; Sunawan, Sunawan; Japar, Muhammad (Study Program of Guidance and Counseling, Postgraduate Program, Universitas Negeri Semarang, 2020)
This study intended to explore the role of empathy as mediator in mediating the relationship between moral disengagement and bullying behavior. The sample of this study was 388 students selected using Cluster Random Sampling technique. To collect the data this study used three instruments, namely Moral Disengagement Scale (MDS), Form Bullying Scale ? Perpetration (FBS ? P), and Interpersonal Reactivity Index (IRI) instruments. Meanwhile, to analyze the data this study used bootstrap mediator analysis technique corrected by method (N = 5000) with the confidential interval of 95%. The results of this study showed that moral disengagement predicted the tendency of bullying and empathy on students. Then, empathy mediated moral disengagement and tendency of bullying on students. These findings provide understanding for guidance and counselling teachers about the effect of empathy in mediating moral disengagement and bullying on students